Arab Republic of Egypt : 2017 Article IV Consultation, Second Review Under the Extended Arrangement Under the Extended Fund Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Egypt's reform program, supported by the Extended Fund Facility arrangement, has played a critical role in stabilizing the economy. By the end of 2015/16, a long-standing and ultimately unsustainable policy mix had resulted in low growth and investment, elevated general government debt, an overvalued exchange rate, a widening current account deficit, declining gross international reserves and severe shortages of foreign exchange. Egypt's economic outlook is favorable, provided prudent macroeconomic policies are maintained and the scope of growth-enhancing reforms is broadened. To sustain economic reform momentum, in the medium term, policy priorities should aim to raise potential output and promote inclusive growth to create jobs for Egypt's young and growing population.